2006
DOI: 10.4141/p06-034
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters, neuroregulators and neurotoxins in the life of plants

Abstract: Cao, J., Cole, I. B. and Murch, S. J. 2006. Neurotransmitters, neuroregulators and neurotoxins in the life of plants. Can. J. Plant Sci. 86: 1183-1188. Recent evidence has shown that neurologically active compounds play an important role in the physiology of higher plants. The human neurotransmitter melatonin (N-acetyl-5-methoxytryptamine) has been found in more than 140 different plant species and is associated with flower and seed development, reproductive capacity and root growth. Hyperforin, once thought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In 1995, Dubbels et al and Hattori and colleagues demonstrated the presence of MT in plants. Since then, it has been found in more than 140 different plant species . MT has also been found in numerous taxa, including fungi, bacteria, protozoans, and invertebrates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, Dubbels et al and Hattori and colleagues demonstrated the presence of MT in plants. Since then, it has been found in more than 140 different plant species . MT has also been found in numerous taxa, including fungi, bacteria, protozoans, and invertebrates .…”
Section: Introductionmentioning
confidence: 99%
“…An elevation of MT in reproductive tissue, with declining MT level as the plant ages, was observed in Pharbitis nil [25]. The accumulation of MT in reproductive tissues, seeds and fruits, may be indicative of a mechanism for protection of the tissues from oxidative damage arising from drought, cold, heat, UV light, or environmental toxins [6,26].…”
Section: Introductionmentioning
confidence: 99%
“…Bip), skullcap (Scutellaria baicalensis Georgi), and devilʼs trumpet (Datura metel L.) [17,18]. Although the exact role for these neurochemicals is yet to be fully understood, potential roles for MEL and 5HT in plant and human tissues include detoxification of free radicals [19,20] and/or hormonal signaling pathways [21][22][23].…”
Section: Abbreviationsmentioning
confidence: 99%
“…Thereafter, MT was considered exclusively as an animal hormone, specifically a neurohormone for nearly four decades until the discovery in plants. Since then, it has been found in more than 140 different plant species and foods [14][15][16][17][18][19][20][21][22][23][24]. MT usually appears in the presence of its precursors; therefore, their simultaneous determination may be extremely important to understand its biosynthesis pathway and biological function in plants.…”
Section: Introductionmentioning
confidence: 99%